Self‐Assembled Protective Layer by Symmetric Ionic Liquid for Long‐Cycling Lithium–Metal Batteries. Issue 13 (10th February 2022) - Jang, Jinha; Shin, Jae‐Sun; Ko, Sunghyun; Park, Hyunchang; Song, Woo‐Jin; Park, Chan Beum; Kang, Jiheong
Abstract: Modulating lithium metal deposition is vital for the realization of stable and energy‐dense Li–metal batteries. Ionic liquid (IL) has been regarded as a promising electrolyte additive for a uniform Li deposition because its cation moiety forms a lithiophobic protective layer on Li protuberant tips. Despite recent advances in ILs for Li metal batteries, rational designs for IL additives are still in their infancy, and further improvement is required. Here, a new class of self‐assembled protective layer based on the design of a new IL molecule enabling high‐performance Li–metal batteries is reported. For the first time, symmetric design of lithiophobic side chains is introduced to the IL cations. This symmetric design creates a self‐assembled lithiophobic protective layer on Li protuberant tips, resulting in the smooth deposition of Li. Thus, the symmetric IL enables stable cycling of Li–LiFePO4 and Li–LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) batteries with an average Coulombic efficiency of ≈ 99.8% over 600 cycles. In addition, the symmetric IL enables a practical thin Li (40 µ m)‐NCM622 cell with an energy density of ≈ 658 Wh kg ‐1 based on the cathode mass in a coin‐type battery. This work proposes a design protocol for IL‐based additives and provides a prospective way to highly efficient, long‐lasting Li–metal batteries. Abstract : A novel ionic liquid (IL) modified by symmetric alkyl chains is employed as an electrolyte additive to control Li deposition. The symmetric alkyl chains to IL cation mitigate the self‐agglomeration and create a densely assembled lithiophobic layer on protuberance tips. This compact protection layer formed by symmetric ILs effectively controls the smooth Li deposits, enabling long‐lasting, practical, and full‐cell batteries.